3v-1=6v-49

Simple and best practice solution for 3v-1=6v-49 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3v-1=6v-49 equation:


Simplifying
3v + -1 = 6v + -49

Reorder the terms:
-1 + 3v = 6v + -49

Reorder the terms:
-1 + 3v = -49 + 6v

Solving
-1 + 3v = -49 + 6v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-6v' to each side of the equation.
-1 + 3v + -6v = -49 + 6v + -6v

Combine like terms: 3v + -6v = -3v
-1 + -3v = -49 + 6v + -6v

Combine like terms: 6v + -6v = 0
-1 + -3v = -49 + 0
-1 + -3v = -49

Add '1' to each side of the equation.
-1 + 1 + -3v = -49 + 1

Combine like terms: -1 + 1 = 0
0 + -3v = -49 + 1
-3v = -49 + 1

Combine like terms: -49 + 1 = -48
-3v = -48

Divide each side by '-3'.
v = 16

Simplifying
v = 16

See similar equations:

| 5x^4+6x^3+x^2=0 | | 243-3x^2-3y^2=0 | | D/6=(-7) | | 10t-29=7t-17 | | 10+9=3x+34 | | 3x-1/48 | | x+(x+1)=x-1 | | y3/2-1 | | 8x-9=2+5x | | 7x-9=21+5x | | 12e-(19)=7-e | | (9x-3)=(3x+6) | | 6cos(x)+8sin(x)=5 | | y(y-6)=16 | | 5x^2-9=12x | | 7/5x=49 | | 3(6y+7)+7y= | | f(x)=(x-3)(2x+6) | | Ax-3x=5forx | | 8y-(3+4y)= | | m=4Gz | | 4x^2+7=-11x | | Ac-3x=5 | | 9/10()=18 | | 8v^2=56v | | Ax-3x=c | | 7g-15=41 | | x^3+3x^2-6x+12=0 | | 144-3x=180 | | x^3-3x^2-6x+12=0 | | 9x^2-12x+62=0 | | x*11+11=x*5+83 |

Equations solver categories